Analysis of Molecular classification of Carcinoma Breast by Immunohisto chemistry in a series of core biopsied tissue at a Tertiary Care Hospital - Naznin, Bidoura; Alam, Mahabub; Tarafder, Tanny; Yesmin, Israt; Hafiz, Farzana; Mistry, Sujit; Rana, Masud (Archives of Clinical and Biomedical Research, 2026)
Background: Breast cancer is a heterogeneous disease with diverse biological behavior and clinical outcomes. Molecular classification through immunohistochemistry (IHC) serves as a vital tool for predicting prognosis and tailoring therapy. This study aimed to evaluate the distribution of molecular subtypes by immunohistochemistry (IHC) in core biopsy samples in a Bangladeshi cohort and their correlation with clinicopathological parameters. Methods: 124 invasive breast carcinoma patients who received core needle biopsy at a tertiary care institution (2023-2024) were included. IHC profiling of ER, PR, HER2, and Ki67 was performed, and the tumors were placed into Luminal A, Luminal B, HER2-enriched, and Triple-negative subtypes. Clinicopathological factors, including tumor grade, size, and nodal status, were also investigated. Statistical significance was assessed by chi-square tests (SPSS v26.0). Results: Among 124 patients (median age: 50.2 ± 11.3 years), 46.8% of them had tumors <2 cm, and 80.6% had moderately differentiated (Grade 2) histology. Molecular subtyping revealed Luminal A as the most common subtype (46.0%), followed by Luminal B (26.6%), Triple-negative (17.7%), and HER2-enriched (9.7%). Hormone receptor expression was ER positive in 70.9% and PR positive in 62.0% of tumors, while HER2 overexpression was observed in 25.0%. The Ki67 proliferation index revealed low proliferative activity (<14%) in 51.6% of the tumors, intermediate (14-30%) in 30.6%, and high (>30%) in 17.8%. The upper outer quadrant was the most common location for the tumor (28.2%), and invasive ductal carcinoma represented 93.5% of all tumors. FNA-proved lymph node metastasis was detected in 9.7% of patients, most frequently BI-RADS category 5 lesions (41.9%). Conclusion: MolecularSubtyping of breast cancer in core biopsies by IHC is a feasible stratification technique within resource-limited settings, which detects a significant predominance of hormone-sensitive Luminal A tumors. The high percentage of aggressive subsets (Triple-negative/HER2-enriched) calls for the generation of targeted treatments and extensive screening programs within Bangladesh. These findings are favorable for the inclusion of molecular diagnostics in clinical practice to optimize treatment planning.